Eksistensi Pidana Tutupan dalam Hukum Pidana Indonesia dalam Kaitannya dengan Asas Equality Before The Law - Muhammad Faiz Indriansyah Reza; Yudi Krismen US (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The reintroduction of pidana tutupan (custody penalty) under Article 74 of Law Number 1 of 2023 on the Indonesian Criminal Code has renewed debates concerning its compatibility with the constitutional principle of equality before the law. This study analyzes the legal basis of pidana tutupan and evaluates whether the preferential treatment afforded to offenders acting on honorable motives (Custodia Honesta) is consistent with Article 27 paragraph (1) of the 1945 Constitution. Employing a normative legal approach with statutory analysis and library research, the study critically examines relevant legal norms and constitutional doctrines. The findings suggest that pidana tutupan is not inherently inconsistent with the principle of equality before the law, provided that differential treatment is justified by objective, rational, and universally applicable legal criteria. Nevertheless, the absence of explicit parameters defining “honorable motives” creates significant interpretative ambiguity and increases the risk of arbitrary application. Without clear legal limitations, the provision may evolve into a privileged mechanism benefiting certain groups, particularly political elites, thereby undermining legal certainty and constitutional equality. The study highlights the need for more precise regulatory standards to ensure consistent implementation while safeguarding equal protection under the law.